Linking intrinsic brain dysfunction to behavioral outcomes in combat-exposed males with PTSD symptoms - Harrington, Deborah L.; Shen, Qian; Angeles-Quinto, Annemarie; Nichols, Sharon; Song, Tao; Hansen, Hayden; Yurgil, Kate A.; Lee, Roland R.; Baker, Dewleen G.; Huang, Ming-Xiong (Frontiers in Psychiatry, 2025)
IntroductionExposure to trauma produces abnormal intrinsic brain activity, but its association to stress-related symptom severity is often elusive, and the relationships with co-occurring psychiatric and cognitive changes are poorly understood.MethodsThis study investigated the neurobehavioral mechanisms of persistent disability in male combat-exposed military personnel and veterans with symptoms of post-traumatic stress disorder (CE-PTSD) (n=19) and trauma-exposed healthy controls with similar combat experiences (n=24). Disturbances in intrinsic activity during resting-state fMRI were identified using a whole-brain analytic approach that quantified regional homogeneity (ReHo) and fractional amplitude of low-frequency fluctuations (fALFF). To determine if functional abnormalities were related to changes in brain macrostructure, cortical thickness and gray/white-matter volume were measured. Regional abnormalities in CE-PTSD were identified by comparing measures of brain function and structure between the two groups. The behavioral relevance of regional abnormalities in the CE-PTSD group was then assessed by their correlations with stress and psychiatric symptom severity and cognitive functioning.ResultsDespite the absence of changes in brain structure in CE-PTSD, fALFF was abnormally increased in the right anterior insula/temporal pole (aIn/TP), left aIn, and bilateral parahippocampus (PH), whereas ReHo was reduced in the right inferior temporal gyrus. Greater increases in right aIn/TP fALFF correlated with more severe hyperarousal and impulsivity in CE-PTSD, suggesting ruminative thoughts or negative feelings hamper emotion regulation. Conversely, greater right PH fALFF correlated with lower hyperarousal and depression, signifying an adaptive response to stress that promotes better affective processing. Importantly, regional abnormalities were detrimental for more complex executive functions, consistent with observations that stress impedes cognitive flexibility and inhibitory control due to a persistent reliance on hypervigilant behaviors.DiscussionAn unbiased, efficient and computationally reliable imaging approach identified intrinsic dysfunction in brain regions that may be core features of CE-PTSD. Though larger samples are needed for verification, the preliminary results provide new insights into the associations between regional abnormalities and different facets of emotion regulation and cognition, which in turn may impact an individual’s functional abilities in daily life and responsiveness to psychotherapy.